2019
DOI: 10.4025/actascianimsci.v41i1.42926
|View full text |Cite
|
Sign up to set email alerts
|

Calcium particle size and feeding time influence egg shell quality in laying hens

Abstract: An experiment with Leghorn laying hens was undertaken to determine the effect of oyster shell particle size and feeding time on different production variables, calcium retention, plasma calcium content and egg internal and external quality. Two hundred Leghorn layers (40 weeks old old) were allocated in five dietary treatments with four replicates during ten weeks. Two particle size combinations (wherein 50% of calcium substituted by medium or coarse particles (1-2 mm and 2-4 mm respectively) and two feeding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…As a result of the research, it was determined that 5 % pomegranate pulp increased egg production and had no effect on feed consumption, feed efficiency, and egg weight. The researchers concluded that the increase in egg production was due to the presence of punicic acid in the pomegranate seed pulp (Saki et al, 2014). The number of studies examining the effect of pomegranate seed oil on laying hens is limited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the research, it was determined that 5 % pomegranate pulp increased egg production and had no effect on feed consumption, feed efficiency, and egg weight. The researchers concluded that the increase in egg production was due to the presence of punicic acid in the pomegranate seed pulp (Saki et al, 2014). The number of studies examining the effect of pomegranate seed oil on laying hens is limited.…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (2007) reported that the use of CLA in combination with several other fatty acids improved egg quality. Saki et al (2014) reported that adding different levels of pomegranate seed pulp to the ration had no effect on egg quality criteria.…”
Section: Resultsmentioning
confidence: 99%
“…The enhancement of eggshell quality described in this meta-analysis could be due to the longer retention of coarse particles in the gizzard inducing an extended diffusion of soluble Ca during the night. As eggshell formation lasts approximatively 20 h and mainly takes place during the night, coarse limestone particles reduce desynchronization between availability and requirement of Ca for the eggshell ( Saki et al, 2019 ). Additionally, laying hens receiving coarse limestone mobilize less bone Ca, and also P, than hens receiving fine limestone, in accordance with Gloux et al (2020) .…”
Section: Discussionmentioning
confidence: 99%
“…The best particle size of Ca supplements for layer chickens has been a controversial topic for almost a century (Saki et al, 2019). The particle size of Ca sources used in rations may have an influence on its availability to the laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, using larger particle sizes slows passage through the gastrointestinal tract (Tunç & Cufadar, 2015). This allows dietary Ca to be available for eggshell formation, with lower mobilization of bone Ca by the layer chickens (Saki et al, 2019). A number of research projects have been conducted to assess the effect of limestone, oyster shells, and egg shells as sources of Ca in layer diets and the effect of their particle sizes on egg shell quality (Saunders-Blades et al, 2009;Olgun et al, 2015;Tunç & Cufadar, 2015).…”
Section: Introductionmentioning
confidence: 99%